An insight of dysregulation of microRNAs in the pathogenesis of diabetic kidney disease - Zahari Sham, Siti Yazmin; Abdullah, Maha; Osman, Malina; Seow, Heng Fong (Malaysian Society of Pathologists, 2022)
Background: Worldwide, diabetic kidney disease (DKD) remains the leading cause of chronic kidney disease (CKD) and its successor, the end stage renal disease, both of which constitute major morbidity and mortality concerns. Content: The residual risk of disease progression remains despite the advert of newer therapeutic modalities and current biomarkers. Meanwhile, microRNAs (miRNAs) are small non-coding RNAs, which regulate gene expression post-translationally by binding to specific mRNAs. Circulating miRNAs are increasingly recognised as novel biomarker or therapeutic targets, owing to their unique characteristics, such as their resilience to degradation by endogenous RNases, multiple downstream targets, involvement in biological processes, some degree of tissue specificity, relatively easy access and quantification. Unlike proteins, there are far less miRNAs and mature miRNAs are highly stable, structurally less complex without post-translational modification with high degree of conservation across species. Aberrant expression of miRNAs has been established in both in vitro and in vivo models of DKD. An up-to-date compilation of previous studies involving selected circulating miRNAs in blood and urine samples of DKD patients is discussed herein. Summary: This review highlights the unmet clinical challenges and dysregulation of miRNAs in the pathogenesis of DKD.